Exploring molecular and cellular mechanisms underlying seizures in neurocysticercosis - de Lange, Anja (Department of Human Biology, 2021)
Neurocysticercosis is a disease in which larvae of the tapeworm, Taenia solium, infect the central nervous system of humans. Seizures are the most common symptom of NCC, occurring in between 70 % and 90 % of all symptomatic NCC cases. Neurocysticercosis impacts heavily on the quality of life of patients, and further presents a significant drain on the economic resources of endemic countries. Despite its considerable global impact, the molecular and cellular mechanisms underlying seizures in neurocysticercosis remain largely unknown. In this thesis I have explored novel models for neurocysticercosis by combining mouse hippocampal organotypic brain slice cultures with various preparations of a model parasite, Taenia crassiceps. Utilising these models, I first explored, using patch clamp and local field potential electrophysiology, how Taenia larval extracts directly affect neuronal excitability. I report that extracts of Taenia crassiceps resulted in a significant acute excitation of neurons and triggered seizure-like events in brain slices. Further investigation revealed that this excitation was mediated by the activation of glutamate receptors and that, indeed, the larvae of both Taenia crassiceps and Taenia solium contain and produce levels of glutamate sufficient to explain this effect. Chronic exposure of brain slices to intact, living, larvae did not, however, result in any changes in network excitability. Next, I investigate whether Taenia larvae produce acetylcholinesterases, as these enzymes have the potential to affect neuronal signaling by digesting the neurotransmitter acetylcholine. Ellman's assays, in situ acetylcholinesterase activity assays, and patch clamp electrophysiology reveal that both Taenia crassiceps and Taenia solium larvae produce acetylcholinesterases and that the activity of Taenia acetylcholinesterases is sufficient to digest acetylcholine at a concentration that alters neuronal signaling. Finally, I explore the effect that Taenia larval extracts have on the innate immune cells of the brain, as the responses of these cells can also alter neuronal excitability. Through the measurement of brain slice cytokine release using enzyme-linked immunosorbent assays, I discover that Taenia crassiceps extracts have robust antiinflammatory effects, which involve lipid, protein, and glycan elements. This thesis presents novel findings that reveal ways in which Taenia larvae interact with both neuronal and nonneuronal resident brain cells. It further delves into how these interactions could contribute to seizure generation in neurocysticercosis and proposes some potential new therapeutic approaches to treat seizures in neurocysticercosis.